Crossed pulmonary arteries: An underestimated cardiovascular variant with a strong association with genetic syndromes—A report of 74 cases with systematic review of the literature. Issue 8 (2nd May 2022) - Mastromoro, Gioia; Calcagni, Giulio; Vignaroli, Walter; Anaclerio, Silvia; Pugnaloni, Flaminia; Rinelli, Gabriele; Secinaro, Aurelio; Bordonaro, Veronica; Putotto, Carolina; Unolt, Marta; Digilio, Maria Cristina; Marino, Bruno; et al.
Abstract: Crossed pulmonary arteries (CPAs) represent an uncommon anatomic variant, usually associated with some specific syndromes and conotruncal defects. This finding has been described in 22q11.2 Deletion Syndrome (22q11.2DS). We evaluated the correlation between CPAs and genetic diseases, in order to better define the characteristics of this variant, considered a rare anatomic pattern. An in‐depth analysis of CPAs genotype–phenotype correlations was performed via a literature review. We detected 74 CPAs patients through echocardiography. Of these 74 patients, 35.1% of patients showed additional intracardiac malformations, while 29.7% showed extracardiac vascular anomalies, of which 16.2% were associated with intracardiac defects and 13.5% were not. In all, 62.2% of patients were diagnosed with genetic diseases and 52.2% of them were 22q11.2DS patients. In conclusions, CPAs represent a cardiovascular variant, which is detectable in nonsyndromic individuals, but especially in various genetic syndromes and in particular in 22q11.2DS patients. Data on the real prevalence of this morphology is lacking in literature. Knowledge of this anatomic variant is useful to interpret the unusual course of the pulmonary branches and is helpful information before cardiovascular surgical correction. Moreover, due to the strong association of CPAs with some genetic syndromes, the identification of this anatomic pattern can indicate the utility of a genetic assessment of these patients.